Structural Modeling of Marital Discord and Negative Interactions on Defense Mechanisms with the Mediating Role of Marital Quality of Life in Patients with Diabetes - Hashemi, Fatemeh Sadat; Ali Mahdi, Mansour; Jafari, Alireza (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The aim of this study was to design and test a structural model of marital discord and negative interactions on defense mechanisms with the mediating role of marital quality of life in patients with diabetes. Methods and Materials: This descriptive-correlational study was conducted using structural equation modeling. The statistical population consisted of 384 patients with diabetes who referred to medical centers in Shiraz and were selected through convenience sampling. The research instruments included the Locke and Wallace Marital Adjustment Test, the Couple Interaction Coding System, the Andrews Defense Style Questionnaire, and the Marital Quality of Life Questionnaire. Data were analyzed using SPSS and AMOS software. Findings: The results showed that marital discord and negative interactions have significant direct and indirect effects on defense mechanisms, and marital quality of life plays a significant mediating role in these relationships. Increased marital discord and negative interactions were associated with decreased use of mature defenses and greater tendency toward maladaptive defenses. Conclusion: These findings highlight the importance of improving marital relationships, reducing conflicts, and strengthening marital quality of life in preventing maladaptive defense mechanisms and promoting mental health. Study limitations included the use of convenience sampling, reliance on self-report questionnaires, and lack of full control over clinical and biological variables.